Notes for the Study of the Monastic Jurisdiction in Medieval Galicia: Seigneurial Income, Family-land Bond and Justice (10th-13th centuries) - López Sabatel, José Antonio (Madrygal. Revista de Estudios Gallegos, 2020)
The aim of this paper is to scrutinise the typical jurisdictional rights under which the Galician peasantry used to live and was required to work. For this purpose, the cartularies of thirteen monasteries have been examined in search of the best possible sample of the evolution of these privileges. And thus, the most characteristic kind of seigneurial income, attachment to the land and exercise of justice will be addressed in the following lines, taking into account their origin, essence, development and, therefore, their impact on the daily life of peasant society.